Penentuan Nilai Energy Gap Lapisan Tipis TiO2/C Dengan Menggunakan Metode Touc Plot - Agus Agus; Helga Dwi Fahyuan; Damris M (Jurnal Ilmu Fisika dan Pembelajarannya (JIFP), 2020)
Research has been conducted on the determination of the value of the TiO2/C energy gap using the Touc Plot method. The purpose of this study was to determine the effect of the addition of percent doping C to the energy gap on TiO2. In this study the variation of doping C percent on TiO2 was 0, 0.2, 0.4, and 0.6%. To obtain the energy gap value of TiO2/C, a transmittance test was performed using a UV-Vis spectrophotometer. The data transmission is processed using the swanepoel equation to determine the refractive index and thickness of the TiO2 / C that is used to determine the value of the energy gap using the touc plot method, and obtain each energy gap with each doping variation of 3.2, 2 , 60, 2.77, 3.0 eV. Where with the addition of doping C to TiO2 the value of the gap energy produced decreases. Keywords: TiO2/C, Swanepoel, Energy Gap